2016
DOI: 10.1016/j.midw.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Higher Facebook use predicts greater body image dissatisfaction during pregnancy: The role of self-comparison

Abstract: the potential impact of Facebook on increasing the risk of, or promoting existing poor body image is an important message for those working to support mothers during pregnancy and the postnatal period. Care should be taken when directing mothers to use the site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 81 publications
(84 reference statements)
2
40
2
Order By: Relevance
“…It was reported in the literature that the pregnancy‐related changes in physical appearance (gaining weight fast, changes in skin, varix appearance, edema in hands and feet, etc.) are perceived positively by some women but lead to body dissatisfaction in others . Studies that investigate body perception in pregnancy obtained similar results, and it was observed that women provided different responses to physical changes accompanying pregnancy .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…It was reported in the literature that the pregnancy‐related changes in physical appearance (gaining weight fast, changes in skin, varix appearance, edema in hands and feet, etc.) are perceived positively by some women but lead to body dissatisfaction in others . Studies that investigate body perception in pregnancy obtained similar results, and it was observed that women provided different responses to physical changes accompanying pregnancy .…”
Section: Introductionmentioning
confidence: 84%
“…Especially in recent years, women increasingly started to experience concern regarding weight gains and their appearance in pregnancy. Therefore, although women are aware that gaining weight through pregnancy is a requirement, they may be in a tendency to limit the effects of pregnancy on their body . About 72% of the participants in the IVF group stated that they took precautions or initiatives (being careful about what they eat, exercising and using skin crack cream) for changes that take place in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hicks and Brown [35] found that time spent on social media was associated with body dissatisfaction among pregnant women.…”
Section: Impact On Women's Health Behavioursmentioning
confidence: 99%
“…Still, the way Internet and media focuses on the "yummy mummy", a slender woman with a neat bump [35], may have impacted the women's GWG.…”
Section: Impact On Women's Health Behavioursmentioning
confidence: 99%